EFEKTIFITAS MANAJEMEN KURIKULUM KELAS KETERAMPILAN DI MADRASAH ALIYAH NEGERI 1 TEGAL - Hayatul Mukarromah; Kurroti A’yun (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2021)
The progress of a nation is very much determined and influenced by the quality of human resources (HR) which is the most important position in development efforts in a nation, the development of science and technology in the increasingly global era also has an influence in all areas of human life. Therefore, it requires the readiness of quality human resources (HR) so that they are able to compete in a global era that is getting tougher with other countries. The quality of human resources in a nation is greatly influenced by the level of education and management formed by a nation. In order to meet future needs and welcome Indonesia's Golden Generation in 2045, a Competency Standard for Graduates based on XXI Century Competencies, Indonesia's Demographic Bonus, and Indonesia's Potential to become the Group of 7 of the World's Largest Economic Countries has been established, and at the same time strengthens Indonesia's contribution to the development of world civilization. General knowledge and skills must be possessed by every human being as a provision for life in this world to lead to happiness in this world and the hereafter. The existence of the Madrasah Aliyah Skills Program is based on the premise that in modern life everyone is required to adapt to the changing times that are always changing rapidly in relations between nations and mobility of employment opportunities. Therefore, this study aims to determine the effectiveness of curriculum management in the provision of skills class programs, especially in skills classes, because the outline does not only know the achievements of students in the academic field, but also includes students' skills. The method used in this research is quantitative method, with the research design of One-shot Case Study. With the sample used were class XII students who participated in the culinary skills program. The data collection technique in this study was carried out using a questionnaire method. After the data has been collected, before the analysis is carried out, the data instrument test is conducted first, namely the validity test. In this study, the validity test used an internal validity test through three experts. From the results of data analysis through the one sample t-test comparative test in this study, it was found that curriculum management on student learning achievement of Madrasah Aliyah Negeri 1 Tegal had significant effectiveness, with significant results (2-tailed) = 0,000. Keywords: Curriculum Management, skills classes